Pengaruh Model Problem Based Learning Terhadap Hasil Belajar Peserta Didik Pada Materi Sistem Pencernaan Manusia Kelas V SD Negeri Lamsayuen Aceh Besar - Susilawati susilawati; Ahadin Ahadin; Suci Fitriani (Elementary Education Research, 2023)
The purpose of this study was to determine the significant effect of the use of problem-based learning models on student learning outcomes in the material of the Human Digestive System Class V, SD Negeri Lamsayue, Aceh Besar. The approach taken is a quantitative approach with True Experimental and Pretest Posttest Control Group Design. The research was conducted in Class V of SD Negeri Ramsayuen Aceh Besar. Sampling was 25 VA students in the experimental class and 25 VB students in the control class using simple random sampling technique. The test used was 20 multiple choice questions for data analysis techniques using SPSS Statistics 26 and hypothesis testing using paired sample T-test. The value of the hypothesis test using the paired sample t test statistic produces a significance value (2-tailed) of 0.000 0.000. 0.05. So the determining criterion is that Ha is accepted and Ho is rejected. Therefore, it can be interpreted that the influence of the problem-based learning model has a significant effect on student learning outcomes in the material of the Human Digestive System Class V, SD Negeri Lamsayue, Aceh Besar.